Mitigasi Kesejahteraan dalam Industri Pertanian Pasca Pelebaran Sungai Batang Merao di Kabupaten Kerinci dan Kota Sungai Penuh - Kurniawan, Bambang; Fusfita, Nurlia (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the impact of the Batang Merao River widening policy on agricultural productivity and the socio-economic welfare of the community around the Batang Merao River. A qualitative approach was used to collect data from 4 (four) sub-districts in Kerinci Regency and Sungai Penuh City that were affected by the Batang Merao River widening policy. The results of the study's mitigation found that the river widening policy had various impacts. On the one hand, the larger water flow capacity helps prevent major flooding, but on the other hand, there is a decrease in soil quality and a higher dependence on climate conditions. In addition, many farmers experienced a decrease in productivity due to disruptions to the more unpredictable irrigation cycle. The results of the study also found that the social impact of this policy involved significant economic losses for farmers, as reflected in decreased income and increased production costs. The surrounding community also experienced environmental damage that affected health conditions and access to clean water.